How School Principal’s Humility Encourages Teachers to Be More Innovative : The Role of Informal Learning and Psychological Safety as Mediators - Qotrunnada, Rifdah; Etikariena, Arum (LPPM Universitas Pendidikan Mandalika, 2025)
This study aims to examine how principals’ leader humility influences teachers’ innovative work behavior through the mediating roles of psychological safety and informal learning. This study used a quantitative survey method. There were four instruments used, including Teacher Innovative Work Behavior Scale, Expressed Humility Scale, Individual Psychological Safety Scale, and Informal Learning Scale. Data were collected from 221 teachers in Indonesia using a convenience sampling technique. Hypotheses were tested using Model 6 of the Hayes PROCESS macro. All hypotheses were supported by the data, indicating that the effect of leader humility on innovative work behavior is mediated by psychological safety (β = 0.06; 95% CI = [0.03, 0.11]), informal learning (β = 0.09; 95% CI = [0.02, 0.15]), and serial mediation of psychological safety and informal learning (β = 0.07; 95% CI = [0.03, 0.12]). These findings highlight the importance of school principal training focused on humility, interpersonal risk management training for teachers, the establishment of teacher learning groups, and enhancement of school management support for teachers’ innovation processes.